Stuck but Not Immobile. Waiting, (Im)Mobility and Agency of Refugees and Asylum Seekers Along the Balkan Routes - Martini, Chiara (Italian Sociological Review, 2024)
The Balkan route, or rather, the Balkan routes, which in recent years have been crossed by many different people, represent a paradigmatic territory on which practices of control, subjugation and precarisation are experimented to the detriment of those in transit. Their lives are punctuated by dynamics and structures that create a constant tension between mobility and immobility, between acceleration and waiting, with obvious and different consequences on trajectories, migration projects and agency. Greece and the Balkan countries represent two emblematic cases of what certain policies of control and closure can produce, both at a structural and individual level. Starting from a fieldwork carried out in Greece and Bosnia and Herzegovina from August to November 2021, this paper will try to analyze how forced waiting and immobility, imposed by the border regime and by asylum and reception systems, can in fact produce illegality (De Genova, 2004), uncertainty (Griffiths, 2013) and precariousness (Khosravi, 2017). Thanks to the collection of testimonies and stories related to the condition of people stranded in these countries, I will show how the hypermobility produced by these dynamics can also represent a tactic, an attempt to regain control over one’s migratory trajectories and to put an end to temporal and geographical stuckedness.